Reincarnation Symbols in Dustin Thao's You've Reached Sam: Roland Barthes' Semiotic Theory - Wilujeng Asih Purwani; Nabila Putri Chelsia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
This study analyzes the novel You've Reached Sam by Dustin Thao to find the meaning of the reincarnation symbol contained in the novel by using semiotic theory by Roland Barthes. In semiotic theory there are five codes namely hermeneutic code, symbolic code, connotative code, cultural code, and action code. In the five codes, three of them describe the symbol of reincarnation in the story, namely the hermeneutic code, the symbolic code, and the connotative code. This study uses a text-oriented approach that focuses on the meaning of the symbol of reincarnation in the main character by analyzing and describing the symbol of reincarnation. The techniques used in collecting data in this study are Documenting Data, Taking Notes and Close Reading. The results of this study indicate that of Roland Barthes' five semiotic codes, there are three codes described, namely hermeneutic codes, symbolic codes, and connotative codes. where there are 24 symbols that describe reincarnation, the hermeneutic code has 8 symbols, the symbolic code has 12 symbols and, 4 connotative symbols describe the reincarnation of the main character in the novel You've Reached Sam.